Ensaio de germinação de sementes de capim-buffel (Cenchrus ciliares L.) - Silva, U R; Nascimento Jr., D; Gomide, J A; Mendonça, C A G; Assis, F N (Revista Ceres, 2025)
An experiment was carried out at the Federal University of Viçosa, to select the best treatment for increasing the germination of Buffelgrass seeds (Cenchrus ciliaris) at three ages